Examining boys' and girls' health‐related quality of life from the first to the third year of upper secondary school: A prospective longitudinal study - Ingrid Oma Langeland; Ragnhild Sollesnes; Roy Miodini Nilsen; Grethe Almenning; Eva Langeland (Wiley, 2019)
Abstract Aim To examine differences in health‐related quality of life between boys and girls in the first and third years of upper secondary school. Design Prospective longitudinal study. Methods The KIDSCREEN‐10 was used to assess health‐related quality of life. Differences in health‐related quality of life over time were estimated using a linear mixed‐effects model for correlated measurements. Results In the first‐year boys (N = 168) and girls (N = 228) reported a mean health‐related quality of life score of 76.3 (SD 10.7) and 69.8 (SD 11.5), respectively. In the third year, the mean health‐related quality of life score for boys and girls was 73.5 (SD 12.4) and 65.7 (SD 13.3), respectively. Boys had a significant decrease in health‐related quality of life mean score of −2.6 and girls a significant decrease of −3.8 (p < .001) over the 3‐year period. There was no significant difference between boys' and girls' health‐related quality of life changes (p = .39).